2014
DOI: 10.2215/cjn.10371013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lowering LDL Cholesterol on Vascular Access Patency

Abstract: Background and objectives Reducing LDL cholesterol (LDL-C) with statin-based therapy reduces the risk of major atherosclerotic events among patients with CKD, including dialysis patients, but the effect of lowering LDL-C on vascular access patency is unclear.Design, setting, participants, & measurements The Study of Heart and Renal Protection (SHARP) randomized patients with CKD to 20 mg simvastatin plus 10 mg ezetimibe daily versus matching placebo. This study aimed to explore the effects of treatment on vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…A reduction in dialysis access revisions or complications was also observed, but in previous exploratory analyses, this finding was not confirmed in data from the AURORA trial, suggesting that any benefits of lowering LDL-C on vascular access patency are likely to be modest [30]. …”
Section: Discussionmentioning
confidence: 99%
“…A reduction in dialysis access revisions or complications was also observed, but in previous exploratory analyses, this finding was not confirmed in data from the AURORA trial, suggesting that any benefits of lowering LDL-C on vascular access patency are likely to be modest [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Exploratory analyses of 2352 participants with a pre‐existing vascular access from the Study of Heart and Renal Protection (SHARP) trial showed a 13% reduction in vascular access occlusive events in participants treated with simvastatin (20 mg) plus ezetimibe (10 mg) compared to placebo (RR 0.87, 95% CI 0.75‐1.00; P = .05). This finding was not replicated in a post hoc analysis of a RCT of 2439 dialysis patients where 29% receiving rosuvastatin had an occlusive vascular access event vs 28% in the placebo group (RR 1.06, 95% CI 0.91‐1.23) . A case–control study of 60 incident dialysis patients suggested a treatment benefit of folic acid and/or statin on primary patency loss of AVFs compared to nonuse .…”
Section: Clinical Trials Of Statin Therapy and Vascular Access Outcommentioning
confidence: 97%
“…Our search identified one RCT and six RCS with chronic renal failure undergoing HD therapy using AVFs (7,(12)(13)(14)(15)(16)(17). We present reasons for study exclusion and progress through stages in Figure 1.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…The AURORA trial was an international, multicenter, large-scale statin trial among hemodialysis patients (25). To test the effect of statins on AVFs vascular access patency, Herrington et al performed a retrospective cohort study using the AURORA database (14), finding that there was no significant effect on vascular access occlusive events (28.9%) in the 1219 HD patients using rosuvastatin versus (27.6%) in the 1220 HD patients using placebo (P = 0.44) during a median 4.5 years of follow-up. Due to the available trial data not confirming a clear benefit of statins therapy on vascular access patency, we carried out the present large-scale meta-analysis.…”
Section: Statins For Arteriovenous Fistulasmentioning
confidence: 99%